Linking Contractor-Supplier Commitment in the Relationship of Customer Orientation, Channel Member and Company Performance in the Construction Industry - Noorhanaliza Mohtar; Sofiah Abd Rahman (International Journal of Supply Chain Management, 2019)
Construction is one of the industries that contribute to the Malaysian economy. Nevertheless, the Malaysian construction industry needs to continuously enhance its value chain efficiency and effectiveness to be a total solution provider in the globalised environment. The purpose of this paper is to establish a link between customer orientation, contractor supplier relationship and company performance. To allow for greater understanding in the field of supply chain management, this study observed into the relationship between the construction companies and their main building materials suppliers. This study employed the quantitative method where stratified random sampling and 235 self-administrated questionnaires were sent to respondents in the construction industry. The cronbach alpha for each dimension namely customer orientation, channel member relationship and company performance are 0.772, 0.616 and 0.838 respectively. The results revealed that customer orientation have positive and significant effects on contractor supplier relationship. It was also found that contractor supplier relationship has significant positive relationship towards company performance. This study focused solely on the companies in the construction industry and data collection was on a single respondent basis. The findings of this study underlines some implication and suggests that construction industry players adopt and emphasise such orientations in order to enhance their performance operational and customer performance in particular. Future study may explore other industry and how it influenced channel members commitment to enhance company performance. Keywords: Malaysia, Construction Industry, Supply Chain Management, Channel Member Relationship, Company Performance